AFFECT OF A NEW AGENT FOR THE ORAL CARE UNDER CONDITIONS OF X-RAY STOMATITIS - L.S. Kravchenko; A.О. Bass; E.L. Zagradskay (Український стоматологічний альманах, 2018)
Inspite of high quality of methodical and technical means of X-ray therapy, X-ray stomatitis development is the basic problem in management of anti-cancer therapy. It takes place in patients who had X-ray therapy associated with cancer at the region of head and neck. And prophylaxis and medical treatment of radiation defeats are not always effective.